2022
DOI: 10.1007/s10584-022-03462-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change implications for olive flowering in Crete, Greece: projections based on historical data

Abstract: Climate change is expected to pose major challenges for olive cultivation in many Mediterranean countries. Predicting the development phases of olive trees is important for agronomic management purposes to foresee future climate impact and proactively act toward adaptation and mitigation strategies. In this study, a statistical model was developed based on winter chill accumulation and, in sequence, on heat accumulation to assess the changes in flowering occurrence for Olea europaea cv. Koroneiki, in the islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…𝐷 𝑖,𝑗,𝑘 = 𝐼 𝑖,𝑗 × 𝛦 𝑖,𝑗,𝑘 (15) where Di,j,k: average annual damages (€/year) per extreme event j and crop i for the k com-bination of RCP climate change scenario and period (k: hist, RCP2.6 2021-2040, … , RCP8.5 2041-2060), Ii,j: damage value (in €) per extreme event indicator j and crop i from equation (14), and Εi,j,k: average annual value of the extreme event indicator j and crop i for the k combination of RCP scenario-time period.…”
Section: Estimation Of Direct Economic Effects Due To Extreme Weather...mentioning
confidence: 99%
“…𝐷 𝑖,𝑗,𝑘 = 𝐼 𝑖,𝑗 × 𝛦 𝑖,𝑗,𝑘 (15) where Di,j,k: average annual damages (€/year) per extreme event j and crop i for the k com-bination of RCP climate change scenario and period (k: hist, RCP2.6 2021-2040, … , RCP8.5 2041-2060), Ii,j: damage value (in €) per extreme event indicator j and crop i from equation (14), and Εi,j,k: average annual value of the extreme event indicator j and crop i for the k combination of RCP scenario-time period.…”
Section: Estimation Of Direct Economic Effects Due To Extreme Weather...mentioning
confidence: 99%
“…Recent research has confirmed the impact of climate change on olive cultivation in Greece. For example, Grillakis et al 2022 [30], in a study in Chalkidiki area, reported that for the RCP4.5 and RCP8.5 scenarios, chill accumulation will be reduced by 12.0-22.7%, respectively, for the near future (2021-2060) and 22.7-70.9% for the far future (2061-2100) compared to the reference period 1979-2019. In addition, flowering will occur 6-10 days earlier in the near future and 12-26 days earlier in the far future, depending on the elevation and the climate change scenario.…”
Section: Olivesmentioning
confidence: 99%
“…The 2015 Paris Agreement establishes a global framework for constraining global warming to below 2°C, with a preferred target of 1.5°C, relative to preindustrial levels (Grillakis et al, 2022). To achieve this temperature objective, nations strive to curb the increase in greenhouse gas emissions as soon as possible and subsequently implement rapid reductions, based on the best available science and considerations of economic and social feasibility (Everest Base Camp Trek | Everest Base Camp Trek Cost 2024-2025.…”
Section: Introductionmentioning
confidence: 99%